A Comparative Study of Status of Awareness of RPwD Act 2016 for Inclusive Education in Government and Private Schools of Chandigarh, Panchkula and Mohali - Bansal, Sneh (INDIAN EDUCATIONAL REVIEW, 2022)
The Rights of Person with Disabilities Act, 2016 supports the concept of Inclusive Education and the action plans of the education sector have prioritised educational access to children with special education needs by making compulsory the necessary arrangements. This includes the creation of a barrier free environment, adaptations in curriculum, teaching methods and evaluation procedures, engagement of specialist teachers, and ensuring the availability of specific teaching and learning material in regular schools. Further, to meet these challenges, government at Central and State levels have introduced procedures, benefits and concessions to children with disabilities.